Prediction of carpal tunnel syndrome using the thenar muscle cross-sectional area by magnetic resonance imaging. Issue 41 (15th October 2021) - Yi, Jungmin; Jeong, Hye-Won; Cho, Hyung Rae; Kang, Keum Nae; Lee, Jonghyuk; Lee, Sooho; Cho, Jaeho; Bang, Yun-Sic; Kim, Young Uk
Abstract : Abstract: Carpal tunnel syndrome (CTS) is a common neuropathy. Although CTS progression is known to be associated with thenar muscle (TM) atrophy, the diagnostic value of TM atrophy for CTS has not been established. In this research, the thenar muscle cross-sectional area (TMCSA) was evaluated to analyze the relationship between the TMCSA and CTS. We assumed that TMCSA is a major diagnostic parameter in the CTS. Both TMCSA and thenar muscle thickness (TMT) samples were acquired from 18 CTS patients, and from 18 control subjects who underwent wrist magnetic resonance imaging with no evidence of CTS. T2-weighted transverse magnetic resonance imaging images were obtained. We measured the TMCSA and TMT at the level of first carpometacarpal joint. The average TMCSA was 296.98 ± 49.39 mm 2 in the normal group and 203.36 ± 72.13 mm 2 in the CTS group. The average TMT was 8.54 ± 1.45 mm in the normal group and 7.38 ± 1.14 mm in the CTS group. CTS group had significantly lower TMCSA and TMT. Receiver operator characteristics curve analysis showed that the best cutoff point for the TMCSA was 260.18 mm 2, with 77.8% sensitivity, 77.8% specificity. The best cutoff point of the TMT was 7.70 mm, with 61.1% sensitivity, 66.7% specificity. Although the TMCSA and TMT were both significantly associated with CTS, the TMCSA was a much more sensitive measurement parameter. Thus, to evaluate CTS patients, the physician should more carefully inspect the TMCSA than TMT.